The Assessment of Groundwater Vulnerability towards Contamination using the DRASTIC and NV Indexes in Banjarbaru City, South Borneo, Indonesia - Firza Syarifa Zahra; Thomas Triadi Putranto (Indonesian Journal of Geography, 2021)
The current excessive use of groundwater is exacerbated by human activities, which directly or indirectly trigger surface pollution and gradually affect to the subsurface, including groundwater. Indonesia is one of the developing countries that encounter these obstacles, specifically Banjarbaru City in South Kalimantan Province and its surroundings. Hence, proper management is needed to maintain the sustainable function of groundwater, such as by determining its vulnerability index to pollution. This study used geospatial analysis to determine the intrinsic and extrinsic vulnerability of groundwater via the DRASTIC and NV index methods, respectively, through visual representations on a map. The validation involved the distribution of nitrate and nitrite values to review the relationship between vulnerability levels and the presence of anthropogenic influences. Subsequently, the results of the DRASTIC method showed that the study area is included in three vulnerability indexes, namely low (95-120), medium (120-160), and high (160-186). The NV method further indicated that the groundwater vulnerability indices are divided into four, namely very low (21.2-70), low (70-110), moderate (110-150), and high (150-186). Based on the results, the use of specific vulnerabilities was considered more effective than the intrinsic technique in determining the vulnerability index because the NV method considers land use as a parameter to provide more detailed outcomes.